Alterações genéticas de cistos e tumores odontogênicos - Elisa Carvalho de Siqueira (2019)
Odontogenic tumors and delevopmental cysts are rare and most of them show uncertain pathogenesis. The use of next generation sequencing techniques (NGS) help to identify pathogenic driver mutations of different tumors. Little is known about the molecular pathogenesis of glandular odontogenic cyst (GOC), odontogenic carcinoma with dentinoid (OCD), and odontogenic myxoma (OM). The present study aimed to investigate the molecular pathogenesis of these three odontogenic lesions. To investigate the mutational profile of GOC, OCD we used a panel of hotspot mutations in 50 oncogenes and tumor suppressor genes, submitted to NGS. The pathogenic variants were validated by Sanger sequencing. This hotspot panel had already been used in OM, but no recurrent pathogenic mutations were identified. Considering that OM shows morphological similarities with intraosseous myofibromas and these lesions exhibit mutations in PDGFRβ, Sanger sequencing was performed in OM samples to assess hotspot mutations in PDGFRβ. Immunohistochemistry was performed in OCD cases to assess whether mutations detected in the CTNNB1 and APC genes impacted the localization of the β-catenin protein. No pathogenic mutations were detected in GOC. We identified pathogenic mutations in CTNNB1 and APC genes in OCD, both components of the WNT-signaling/β-catenin pathway. Consistent with activation of this signaling pathway, the tumors showed strong β-catenin accumulation mainly in the cytoplasm of neoplastic cells. The OM samples did not show PDGFRβ mutations. Pathogenic mutations in the tumor suppressor genes and oncogenes studied do not seem to explain the pathogenesis of GOC. Activating mutations of the β-catenin pathway appear to be important events in the pathogenesis of OCD. The absence of mutations in PDGFRβ in OM indicates a difference in the pathogenesis of this tumor and myofibroma. Further studies with larger gene panels or whole exome sequencing are needed to investigate whether recurrent pathogenic mutations occur in GOC and OM. In addition, the study of new cases of COD is important to assess whether our results are relevant.